Venezuelan Migration in Latin America: History and sociodemographic aspects. - Alarcón, Renato D. (2022)
The migration of millions of Venezuelans to South American countries in the last two or three decades is one of the most significant social phenomena in the continent’s history. This article presents a brief historical account of the process and describes a variety of dramatic aspects of the migrants’ experiences throughout the long road towards Colombia, Ecuador, Perú and other countries. The main socio-demographic characteristics of the migrant population (numbers, population types, geographic location in the host country, age, gender and civil status, work and employment) in the above three countries, are described as a relevant basis of further inquiries on the repercussions of migration on the mental health of its protagonists. The information covers important aspects of the journey and the arrival as the initiation of a painful and uncertain process of acculturation and adaptation.